ChemInform Abstract: PEG‐Supported Recyclable Catalyst for Enantioselective Ethylations. Issue 29 (1st July 2013) - Zeng, Xiaofeng; Malik, Debasis; Chen, Ryan; Lee‐Ruff, Edward
Abstract Full recovery of the catalyst can be achieved by addition of diethyl ether.